The Development of Solah Chair Using Electronic Sensor to Assist Disabled Muslims in Performing Prayers - Abdullah Solihin Mohd Fauzi; Ahmad Abror Hakim Bin Sa'idan; Juliza Jamaludin; Wan Zakiah Wan Ismail; Irneza Ismail; Mus'ab Sahrim; Bushra Naeem; Ahmad Syahmi Mohd Zain; Farah Aina Mohd Jamal; Syarfa Najihah Raisin (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2020)
AbstractNowadays, the innovation and production of prayer seats can widely be seen around the world particularly in a nation or region with a majority of Muslim population. Demands on this assistive device are everywhere in order to ease and help disabled Muslims to conduct their daily prayers. Most of the existing devices consist of basic systems and sometimes do not accurately meet disabled Muslims’ requirement. The main objective of this research is to design and develop a Solah chair using electronic sensor to assist disabled Muslims to perform Solah and other ritual activities comfortably. This research uses four types of electrical and electronic systems namely the ultrasonic system, DF player system, counter system and IR sensor system to assist disabled Muslims to perform Solah and other ritual activities such as zikir and listening to Quran recitation. Arduino Uno is used to integrate these four subsystems. Arduino as the main micro-controller for this system is chosen for its convenience and capabilities to read and run C-language. It is also a simple platform which is suitable for many IT projects in general.